2014
DOI: 10.1002/jib.155
|View full text |Cite
|
Sign up to set email alerts
|

Increased protein-thiol solubilization in sweet wort by addition of proteases during mashing

Abstract: The flavour stability of beer is of major concern for breweries and is closely linked to oxidative processes in the beer. In this study, a new approach to boost the antioxidative capacity of beer was investigated. Protease treatment during mashing was performed in order to solubilize or extract more thiol-containing protein-derived compounds into the wort. Five different proteases were tested, and they were all capable of solubilizing increased amounts of thiols in wort during mashing but with different effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In another approach to increase protein-derived thiol concentrations in beer, proteases were added during mashing for increased solubilization of protein-derived thiols into the wort and final beer. , This methodology was shown to increase the amount of free thiols in beer from 37 μM to 57 μM. Sulfur-derived off-flavors were detected by sensory analysis in fresh protease-treated beer, but only to a minor extent and these off-flavors disappeared during storage .…”
Section: Resultsmentioning
confidence: 99%
“…In another approach to increase protein-derived thiol concentrations in beer, proteases were added during mashing for increased solubilization of protein-derived thiols into the wort and final beer. , This methodology was shown to increase the amount of free thiols in beer from 37 μM to 57 μM. Sulfur-derived off-flavors were detected by sensory analysis in fresh protease-treated beer, but only to a minor extent and these off-flavors disappeared during storage .…”
Section: Resultsmentioning
confidence: 99%
“…Comparing the initial level of amino acids (45M1: 2372 mg/L; 45M2: 3278 mg/L; 63M1: 2102 mg/L; 63M2: 1839 mg/L), it was confirmed that the mashing procedure which included a 45°C step increased the free amino acids. The enhanced proteolytic enzyme activity at 45°C results in higher amounts of the reactants (35). Regarding the effect of malt modification (assessed by soluble nitrogen), there was no consistent trend in the sum of amino acids in the initial wort.…”
Section: Sugars and Amino Acids In The Wort Boiling Processmentioning
confidence: 88%